THE CURRENT STATE OF WEB PLATFORMS IN ENHANCING THE PROFESSIONAL COMPETENCE OF FUTURE BIOLOGY TEACHERS - Raupova Mehrinigor Haydarovna; Akramova Moxinabonu Mirg‘olibovna (Web of Journals Publishing, 2025)
This article analyzes the role and current state of WEB platforms in developing the professional competence of pre-service biology teachers amidst the growing importance of digital transformations in the 21st-century education system. A comparative analysis is conducted between the experience of developed countries (e.g., USA, Finland, South Korea) in using WEB platforms in education and the current situation in Uzbekistan. The level of WEB platform utilization in pedagogical higher education institutions in Uzbekistan, infrastructural capabilities, existing challenges, and ways to overcome them are examined, and the potential of these platforms in shaping subject-specific, methodological, and technological competencies is evaluated.
Keywords: pre-service biology teacher, professional competence, WEB platforms, digital education, developed countries, Uzbekistan, TPACK, educational technologies, pedagogical innovation.